ทักษะและปัจจัยในการรู้เท่าทันสื่อสังคมออนไลน์ของเจเนอเรชันอัลฟ่า - อิ่มประเสริฐ กรัณย์พัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This academic article aims to study 1) the patterns of social media usage among Generation Alpha and 2) the skills and factors contributing to Generation Alpha’s social media literacy, using a literature review method. The study found that Generation Alpha exhibits the following patterns in using social media: 1) They are proficient in accessing information and technology via the internet; 2) They have diverse learning styles, but at the same time may face risks such as tech dependence, attention deficit problems, and exposure to unverified information; and 3) They prioritize communication, learning, and interaction on social media. Five essential skills for media literacy are: 1) accessing information, 2) analyzing and evaluating information, 3) creating and communicating content, 4) reflecting on the impact on society and oneself, and 5) taking action to change behavior. Factors influencing children’s media literacy include: 1) technology and content, 2) awareness, 3) perceived values from the media, 4) self-efficacy and confidence, 5) social networks, 6) family context, and 7) educational and workplace environment.